2018
DOI: 10.1080/17435390.2018.1425497
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles induce neurotoxicity in a human embryonic stem cell-derived neuron and astrocyte network

Abstract: Silver nanoparticles (AgNPs) are among the most extensively used nanoparticles and are found in a variety of products. This ubiquity leads to inevitable exposure to these particles in everyday life. However, the effects of AgNPs on neuron and astrocyte networks are still largely unknown. In this study, we used neurons and astrocytes derived from human embryonic stem cells as a cellular model to study the neurotoxicity that is induced by citrate-coated AgNPs (AgSCs). Immunostaining with the astrocyte and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…For example, Kaur and Tikoo 59 reported that the cytotoxicity effect of AgNPs depended on dose, surface potential of nanoparticles, and cells type in skin epithelial A431, lung epithelial A549 and murine macrophages RAW264.7 cells. Repar et al 60 examined the neurotoxicity induced by citrate-coated AgNPs (AgSCs) in neurons and astrocytes originated from human embryonic stem cells. When neurons and astrocytes were exposed to 0.1 μg/mL of AgSCs the astrocyte/neuron ratio is increased and helped astrogenesis, but 5.0 μg/mL of AgSCs significantly changed the morphology of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kaur and Tikoo 59 reported that the cytotoxicity effect of AgNPs depended on dose, surface potential of nanoparticles, and cells type in skin epithelial A431, lung epithelial A549 and murine macrophages RAW264.7 cells. Repar et al 60 examined the neurotoxicity induced by citrate-coated AgNPs (AgSCs) in neurons and astrocytes originated from human embryonic stem cells. When neurons and astrocytes were exposed to 0.1 μg/mL of AgSCs the astrocyte/neuron ratio is increased and helped astrogenesis, but 5.0 μg/mL of AgSCs significantly changed the morphology of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, they suffer from low tissue availability and unrepresentative cellular responses, respectively. A number of recent studies have therefore used human ESC‐derived neural cell models to explore the toxicity of nanoparticles and have demonstrated that stem cells provide an excellent platform for studying the cytotoxicity of nanomaterials (Begum, Aguilar, Elias, & Hong, ; Oh et al, ; Repar et al, ). We were therefore motivated to test the utility of ESC‐derived RPE cells to evaluate the cytotoxicity of GO nanosheets and to compare their responses to two commonly used models: primary hRPEs and ARPE19 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, more information is needed about the toxicity of the conductive inks used in the neural regeneration system, including threshold limits, safe doses, and biocompatibility. For instance, although nanoscale silver particles are now in widespread use in a variety of commercial products, these particles can cause neurotoxicity, reduced neurite outgrowth, inflammation and oxidative stress . Alternative approaches using noncontact stimuli such as light, magnetic fields, or ultrasound could be promising alternatives for neural stimulation devices …”
Section: Summary Technical Challenges and Outlookmentioning
confidence: 99%